Application features of the electrostatic systems for measuring the secondary electron emission yield - Karpus, S.; Shliahov, I.; Liashchov, M.; Borisenko, V.; Kochetov, S.; Tsiats’ko, E.; Shopen, O. (Problems of Atomic Science and Technology, 2023)
The analysis of the experimental systems for research of secondary electron emission during the interaction of electron beams with matter is presented. The three most common and methodologically developed variants of exper-imental systems are considered. According to their design features and methodological capabilities, they allow for the study of the main parameters of secondary emission depending on the primary electron beam energy and the sample thickness. The evolution of the experimental measuring systems and their improvement from simple to three-electrode systems with pass-through collectors is considered too. The peculiarities of registration of the sec-ondary electrons current emitted from the studied target surface depending on the structural features of the target device are considered too. Application results of the developed three-electrode measuring system for research thin foil emission characteristics have been discussed. Проведено аналіз експериментальних систем дослідження вторинної електронної емісії при взаємодії електронних пучків з речовиною. Розглянуто три найбільш поширені та методологічно розроблені варіанти експериментальних систем. За своїми конструктивними особливостями та методичними можливостями вони дозволяють досліджувати основні параметри вторинної емісії залежно від енергії первинного електронного пучка та товщини зразка. Розглянуто еволюцію експериментальних вимірювальних систем та їх удосконалення від простих до триелектродних систем з прохідними колекторами. Розглянуто також особливості реєстрації струму вторинних електронів у залежності від конструктивних особливостей пристрою мішені. Обговорено результати застосування розробленої триелектродної вимірювальної системи для дослідження емісійних характеристик вторинних електронів з тонкої плівки.